(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Most of the morphological and physiological studies are focused on morphological changes in the heart and pancreas. There are few studies devoted to the morphological changes of female reproductive organs in the case of metabolic syndrome. Taking into account the above, we studied the morphological changes in the uterus as an object of research. In the obtained results, the main morphological substrate was the changes in the appearance of destruction and defragmentation of the uterus.